Same evidence different recommendations: a methodological assessment of transatlantic guidelines for the management of valvular heart disease - Milojevic, Milan; Sousa-Uva, Miguel; Marin-Cuartas, Mateo; Kaul, Sanjay; Nikolic, Aleksandar; Mandrola, John; Sádaba, J Rafael; Myers, Patrick O (European journal of cardio-thoracic surgery, 2024)
Summary OBJECTIVES The aim of this study was to identify methodological variations leading to varied recommendations between the American College of Cardiology (ACC)/American Heart Association (AHA) and the European Society of Cardiology (ESC)/European Association for Cardio-Thoracic Surgery (EACTS) valvular heart disease guidelines and to suggest foundational steps towards standardizing guideline development. METHODS An in-depth analysis was conducted to evaluate the methodologies used in developing the transatlantic guidelines for managing valvular heart disease. The evaluation was benchmarked against the standards proposed by the Institute of Medicine. RESULTS Substantial discrepancies were noted in the methodologies utilized in development processes, including Writing Committee composition, evidence evaluation, conflict of interest management and voting processes. Furthermore, despite their mutual differences, both methodologies demonstrate notable deviations from the Institute of Medicine standards in several essential areas, including literature review and evidence grading. These dual variances likely influenced divergent treatment recommendations. For example, the ESC/EACTS recommends transcatheter edge-to-edge repair for patients with chronic severe mitral regurgitation ineligible for mitral valve surgery, while the ACC/AHA recommends transcatheter edge-to-edge repair based on anatomy, regardless of surgical risk. ESC/EACTS guidelines recommend a mechanical aortic prosthesis for patients under 60, while ACC/AHA guidelines recommend it for patients under 50. Notably, the ACC/AHA and ESC/EACTS guidelines have differing age cut-offs for surgical over transcatheter aortic valve replacement (<65 and <75 years, respectively). CONCLUSIONS Variations in methodologies for developing clinical practice guidelines have resulted in different treatment recommendations that may significantly impact global practice patterns. Standardization of essential processes is vital to increase the uniformity and credibility of clinical practice guidelines, ultimately improving healthcare quality, reducing variability and enhancing trust in modern medicine. Valvular heart diseases (VHDs) present a major healthcare challenge globally as they substantially elevate the risk of mortality and severe morbidity, thereby contributing significantly to a decline in quality of life in patients at all ages [1–3]. Graphical abstract